Corrosion behaviour of WC hardmetals with nickel-based binders. (February 2019) - Rocha, A.M. Ferro; Bastos, A.C.; Cardoso, J.P.; Rodrigues, F.; Fernandes, C.M.; Soares, E.; Sacramento, J.; Senos, A.M.R.; Ferreira, M.G.S.
Highlights: WC hardmetal composites with Ni-based binders have been synthesised. The mechanical properties are comparable to the WC-Co benchmark. WC-NiCrCoMo and WC-NiCrMo composites show passive behaviour in 0.5 M NaCl. Abstract: Cobalt is the standard binder in tungsten carbide (WC) hardmetals due to its compatibility with the WC phase, resulting in composites with exceptional hardness and wear resistance. However, their corrosion resistance is not satisfactory in many applications, leading to the early deterioration and failure of tools and equipment. In this work, the corrosion of WC hardmetals with three alternative binders (FeCoNi, NiCrCoMo and NiCrMo) is compared with a benchmark WC-Co composite, using electrochemical techniques such as open circuit potential (OCP) monitoring, polarisation curves and electrochemical impedance spectroscopy (EIS), assisted by scanning electron microscopy (SEM).